THEORETICAL-APPLIED BASES OF CORRECTIVE DIAGNOSTICS IN HIGHER EDUCATION INSTITUTIONS - Svitlana Martynenko (Borys Grinchenko Kyiv Metropolitan University, 2019)
The article deals with the problem of corrective diagnostics functioning in institutions of higher education, analyzes the basic concepts of pedagogical diagnostics development, its main functions; the essence and peculiarities of diagnostic activity of the university teacher are revealed. We define the corrective function of pedagogical diagnostics as didactic correction of the educational process of the university; as a psychological and pedagogical correction of the teacher's activity and mobility in the process of self-development and self-realization. The components of the corrective function are: psychological (correction of student behaviour); correction of student' knowledge in the process of obtaining education as a result of the didactic decision of the teacher based on the application of diagnostic procedures; correction of knowledge of future professionals due to diagnostic procedures. The author pays special attention to the components of the diagnostic correction function, the peculiarities of its implementation in the educational process of the university, its influence on the professional formation of the personality, the individualization of the educational environment. Specific examples of correction diagnostics at Kyiv International University are presented in order to monitor students' academic achievement; the difficulties and the algorithm of their overcoming are analyzed; peculiarities of conducting diagnostic testing and questionnaire of students of multidisciplinary university are revealed, prospects of further researches are determined. Prospects for further research are the development and testing of individual diagnostic correction techniques.